Acute UV Irradiation Increases Heparan Sulfate Proteoglycan Levels in Human Skin - Jung, Ji-Yong; Oh, Jang-Hee; Kim, Yeon Kyung; Shin, Mi Hee; Lee, Dayae; Chung, Jin Ho (Journal of Korean medical science, 2012)
Glycosaminoglycans are important structural components in the skin and exist as various proteoglycan forms, except hyaluronic acid. Heparan sulfate (HS), one of the glycosaminoglycans, is composed of repeated disaccharide units, which are glucuronic acids linked to an N-acetyl-glucosamine or its sulfated forms. To investigate acute ultraviolet (UV)-induced changes of HS and HS proteoglycans (HSPGs), changes in levels of HS and several HSPGs in male human buttock skin were examined by immunohistochemistry and real-time quantitative polymerase chain reaction (qPCR) after 2 minimal erythema doses (MED) of UV irradiation (each n = 4-7). HS staining revealed that 2 MED of UV irradiation increased its expression, and staining for perlecan, syndecan-1, syndecan-4, CD44v3, and CD44 showed that UV irradiation increased their protein levels. However, analysis by real-time qPCR showed that UV irradiation did not change mRNA levels of CD44 and agrin, and decreased perlecan and syndecan-4 mRNA levels, while increased syndecan-1 mRNA level. As HS-synthesizing or -degrading enzymes, exostosin-1 and heparanase mRNA levels were increased, but exostosin-2 was decreased by UV irradiation. UV-induced matrix metalloproteinase-1 expression was confirmed for proper experimental conditions. Acute UV irradiation increases HS and HSPG levels in human skin, but their increase may not be mediated through their transcriptional regulation.